Antibiotic Susceptibility Patterns and Plasmid Profile of Vibrio cholerae from Water Samples in Elele Community, Rivers State, Nigeria - OE Benedicta (Journal of Applied Sciences and Environmental Management)
The antibiotic susceptibility patterns and plasmid profile were studied for 18(32.14%) samples of Vibrio cholerae isolates recovered from water samples from Elele Community. All isolates showed a multiple resistance patterns to 7 antibiotics namely amoxicillin, cotrimoxazole, nitrofurantoin, gentamicin, tetracycline, ampicillin, chloramphenicol and none of the isolates were susceptible to all antibiotics tested. All 56 isolates were sensitive to ofloxacin and ciprofloxacin. The presence of plasmid was screened and out of the 18 isolates only 1(5.5%) harboured plasmid with 2 bands of 1.19kpb and 1.06kpb as molecular weight. @JASEM